Characterising the mountain boundary layer using a passive microwave radiometer - Hannah Scheiber; Mathias W. Rotach; Helen Claire Ward (Bulletin of Atmospheric Science and Technology, 2026)
Microwave radiometers can provide continuous temperature and humidity profiles in the troposphere. This contribution presents data from the long-term deployment (2012–2025) of a passive microwave radiometer in the Inn Valley, Austria. In a first step, an automated quality control procedure was developed and applied to the dataset, resulting in over 42,000 h of data for analysis. Comparison against radiosoundings shows that the microwave radiometer captures the boundary layer temperature structure reliably up to about 1500 m above ground level, with root-mean-square errors (RMSE) of 0.5–1.0 K. At higher altitudes errors increase and a positive temperature bias of up to 1.4 K emerges. Absolute humidity retrievals perform less well overall with RMSE values around 0.6–0.9 g m − 3 in the lowest 1500 m. The microwave radiometer is unable to capture sharp gradients in temperature (or humidity) and thus underestimates positive lapse rates and overestimates negative lapse rates. Next, this long-term dataset is used to investigate the seasonal and diurnal variability of the mountain boundary layer. Analysis of normalised virtual potential temperature profiles highlights the complexity of the valley atmosphere, which frequently deviates from the textbook structure occurring over flat and homogeneous terrain. Above the surface layer, in the warm season a mixed layer develops with a stably stratified layer above, sometimes accompanied by an elevated neutral layer below crest height. The first mixed layer is shallower than expected from studies in flat terrain under comparable conditions. At night, the residual layer, which is typically present over flat terrain, is rarely seen in this dataset. Considerable differences in boundary layer structure during valley-wind days and foehn events are highlighted. Overall, this study demonstrates both the potential and limitations of passive microwave radiometry measurements for boundary layer research in complex terrain.

Characterization of the Surface Energy Balance Residual in Complex Terrain - Martina Destro; Mathias W. Rotach; Manuela Lehner (Boundary-Layer Meteorology, 2026)
The closure of the surface energy balance (SEB) in complex terrain remains a persistent challenge. We present a multi-site analysis based on the i-Box network in the Inn Valley, Austria, to characterize the SEB residual ( Res ) normalized by net radiation ( Rn ) across different conditions. Diurnal cycles of Res / Rn and turbulent fluxes show a significant residual, positive (i.e., an energy gain) during the day and negative (i.e., an energy loss) during the night. Large Res / Rn is observed during nighttime stable conditions, and minimum values are found under convective mixing. Annual cycles show a distinct pattern for most of the sites, with warmer months displaying the smallest Res / Rn during daytime and largest values during nighttime, while colder months are associated with the opposite behaviour. The study examines the influence of atmospheric stability, turbulent mixing and flow conditions on Res / Rn . Results reveal that unstable conditions, associated with higher vertical mixing, tend to reduce the magnitude of Res / Rn . In contrast, stable conditions are linked to larger residuals. Especially for certain stations, foehn events and valley wind days introduce additional variability. Our findings thus point out not only the need to account for atmospheric stability, turbulence structure, and flow regimes, but also the site-specific response of Res / Rn to the above conditions which highlights the importance of collecting spatially distributed complex terrain observations.

Corrigendum to “Agreement of multiple night- and daytime filtering approaches of eddy covariance-derived net ecosystem CO2 exchange over a mountain forest” [Agricultural and Forest Meteorology Volume 356 (2024) 110173] - Alexander Platter; Katharina Scholz; Albin Hammerle; Mathias W. Rotach; Georg Wohlfahrt (Agricultural and Forest Meteorology, 2025)

Agreement of multiple night- and daytime filtering approaches of eddy covariance-derived net ecosystem CO 2 exchange over a mountain forest - Alexander Platter; Katharina Scholz; Albin Hammerle; Mathias W. Rotach; Georg Wohlfahrt (Agricultural and Forest Meteorology, 2024)

Carbon dioxide exchange in an idealized valley - Matthias Reif; Mathias W. Rotach; Alexander Gohm; Georg Wohlfahrt (Environmental Modelling & Software, 2024)

The Performance of a Time-Varying Filter Time Under Stable Conditions over Mountainous Terrain - Manuela Lehner; Mathias W. Rotach (Boundary-Layer Meteorology, 2023)
Eddy-covariance data from five stations in the Inn Valley, Austria, are analyzed for stable conditions to determine the gap scale that separates turbulent from large-scale, non-turbulent motions. The gap scale is identified from (co)spectra calculated from different variables using both Fourier analysis and multi-resolution flux decomposition. A correlation is found between the gap scale and the mean wind speed and stability parameter z / L that is used to determine a time-varying filter time, whose performance in separating turbulent and non-turbulent motions is compared to the performance of constant filter times between 0.5 and 30 min. The impact of applying different filter times on the turbulence statistics depends on the parameter and location, with a comparatively smaller impact on the variance of the vertical wind component than on the horizontal components and the turbulent fluxes. Results indicate that a time-varying filter time based on a multi-variable fit taking both mean wind speed and stability into account and a constant filter time of 2–3 min perform best in that they remove most of the non-turbulent motions while at the same time capturing most of the turbulence. For the studied sites and conditions, a time-varying filter time does not outperform a well chosen constant filter time because of relatively small variations in the filter time predicted by the correlation with mean flow parameters.

Correction to: The Impact of Three-Dimensional Effects on the Simulation of Turbulence Kinetic Energy in a Major Alpine Valley - Brigitta Goger; Mathias W. Rotach; Alexander Gohm; Oliver Fuhrer; Ivana Stiperski; Albert A. M. Holtslag (Boundary-Layer Meteorology, 2023)
The funding agency information in the Acknowledgements was not complete in the original publication of the article. The revised Acknowledgments is provided in this erratum.

Including the Urban Canopy Layer in a Lagrangian Particle Dispersion Model - Stefan Stöckl; Mathias W. Rotach; Natascha Kljun (Boundary-Layer Meteorology, 2022)
In this study we introduce a novel extension of an existing Lagrangian particle dispersion model for application over urban areas by explicitly taking into account the urban canopy layer. As commonly done, the original model uses the zero-plane displacement as a lower boundary condition, while the extension reaches to the ground. To achieve this, spatially-averaged parametrizations of flow and turbulence characteristics are created by fitting functions to observational and numerical data. The extended model is verified with respect to basic model assumptions (well-mixed condition) and its behaviour is investigated for unstable/neutral/stable atmospheric stabilities. A sensitivity study shows that the newly introduced model parameters characterizing the canopy turbulence impact the model output less than previously existing model parameters. Comparing concentration predictions to the Basel Urban Boundary Layer Experiment—where concentrations were measured near roof level—shows that the modified model performs slightly better than the original model. More importantly, the extended model can also be used to explicitly treat surface sources (traffic) and assess concentrations within the urban canopy and near the surface (pedestrian level). The small improvement with respect to roof level concentrations suggests that the parametrized canopy profiles for flow and turbulence characteristics realistically represent the dispersion environment on average.

Cold-Air Pool Processes in the Inn Valley During Föhn: A Comparison of Four Cases During the PIANO Campaign - Maren Haid; Alexander Gohm; Lukas Umek; Helen C. Ward; Mathias W. Rotach (Boundary-Layer Meteorology, 2022)
We present a comprehensive analysis of four south föhn events observed during the Penetration and Interruption of Alpine Foehn (PIANO) field campaign in the Inn Valley, Austria, in the vicinity of Innsbruck. The goal is to detect and quantify processes of cold-air pool (CAP) erosion by föhn as well as processes of föhn breakdown. Despite differences in föhn breakthrough and strength, the four cases exhibit similarities in CAP evolution: initially, the CAP experienced strongest warming in the centre of Innsbruck, where the föhn jet from the Wipp Valley interacted with the CAP in the Inn Valley. The resulting shear-flow instability at the föhn–CAP interface caused turbulent CAP erosion and, together with vertical warm-air advection, led to CAP depression over the city centre. This depression drove pre-föhn westerlies near the surface that caused cold-air advection inside the CAP west of the city centre and warm-air advection in the east. Ultimately, the latter contributed to stronger CAP erosion in the east than in the west. This stronger heating also explains the preferential initial föhn breakthrough at the valley floor east of Innsbruck. In two of the cases, subsequent westward propagation of the föhn–CAP boundary across the city accompanied by northerly (deflected) föhn winds led to a complete föhn breakthrough. Föhn breakdown occurred either by a backflow of the CAP remnant or by a cold-frontal passage. This study emphasizes the importance of both turbulence and advection in the CAP heat budget and reveal their large spatio–temporal variability.

Parametric gridded weather generator for use in present and future climates: focus on spatial temperature characteristics - Martin Dubrovsky; Radan Huth; Hetal Dabhi; Mathias W. Rotach (Theoretical and Applied Climatology, 2020)

A Method to Identify Synoptically Undisturbed, Clear-Sky Conditions for Valley-Wind Analysis - Manuela Lehner; Mathias W. Rotach; Friedrich Obleitner (Boundary-Layer Meteorology, 2019)

Scalar-Flux Similarity in the Layer Near the Surface Over Mountainous Terrain - Eleni Sfyri; Mathias W. Rotach; Ivana Stiperski; Fred C. Bosveld; Manuela Lehner; Friedrich Obleitner (Boundary-Layer Meteorology, 2018)

The Impact of Three-Dimensional Effects on the Simulation of Turbulence Kinetic Energy in a Major Alpine Valley - Brigitta Goger; Mathias W. Rotach; Alexander Gohm; Oliver Fuhrer; Ivana Stiperski; Albert A. M. Holtslag (Boundary-Layer Meteorology, 2018)
The correct simulation of the atmospheric boundary layer (ABL) is crucial for reliable weather forecasts in truly complex terrain. However, common assumptions for model parametrizations are only valid for horizontally homogeneous and flat terrain. Here, we evaluate the turbulence parametrization of the numerical weather prediction model COSMO with a horizontal grid spacing of $$Δ x = 1.1\,\hbox {km}$$ Δ x = 1.1 km for the Inn Valley, Austria. The long-term, high-resolution turbulence measurements of the i-Box measurement sites provide a useful data pool of the ABL structure in the valley and on slopes. We focus on days and nights when ABL processes dominate and a thermally-driven circulation is present. Simulations are performed for case studies with both a one-dimensional turbulence parametrization, which only considers the vertical turbulent exchange, and a hybrid turbulence parametrization, also including horizontal shear production and advection in the budget of turbulence kinetic energy (TKE). We find a general underestimation of TKE by the model with the one-dimensional turbulence parametrization. In the simulations with the hybrid turbulence parametrization, the modelled TKE has a more realistic structure, especially in situations when the TKE production is dominated by shear related to the afternoon up-valley flow, and during nights, when a stable ABL is present. The model performance also improves for stations on the slopes. An estimation of the horizontal shear production from the observation network suggests that three-dimensional effects are a relevant part of TKE production in the valley.

Comment on: “Corrections to the Mathematical Formulation of a Backwards Lagrangian Particle Dispersion Model” by Gibson and Sailor (2012: Boundary-Layer Meteorology 145, 399–406) - Stefan Stöckl; Mathias W. Rotach; Natascha Kljun (Boundary-Layer Meteorology, 2018)

Numerical ragweed pollen forecasts using different source maps: a comparison for France - Katrin Zink; Pirmin Kaufmann; Blaise Petitpierre; Olivier Broennimann; Antoine Guisan; Eros Gentilini; Mathias W. Rotach (International Journal of Biometeorology, 2017)

Erratum to: On the Measurement of Turbulence Over Complex Mountainous Terrain - Ivana Stiperski; Mathias W. Rotach (Boundary-Layer Meteorology, 2016)

On the Measurement of Turbulence Over Complex Mountainous Terrain - Ivana Stiperski; Mathias W. Rotach (Boundary-Layer Meteorology, 2016)

Special issue: 125 years of high-mountain research at Sonnblick Observatory (Austrian Alps) - Hartmut Graßl; Michael Hantel; Mathias W. Rotach; Ernest Rudel (Theoretical and Applied Climatology, 2012)

Building models for daily pollen concentrations - Denis Hilaire; Mathias W. Rotach; Bernard Clot (Aerobiologia, 2012)

On the efficiency and correction of vertically oriented blunt bioaerosol samplers in moving air - Dominik Michel; Mathias W. Rotach; Regula Gehrig; Roland Vogt (International Journal of Biometeorology, 2012)

Flux Footprints Over an Undulating Surface - Weiguo Wang; Mathias W. Rotach (Boundary-Layer Meteorology, 2010)

The Budget of Turbulent Kinetic Energy in the Urban Roughness Sublayer - Andreas Christen; Mathias W. Rotach; Roland Vogt (Boundary-Layer Meteorology, 2009)

Boundary layer characteristics and turbulent exchange mechanisms in highly complex terrain - Mathias W. Rotach; Marco Andretta; Pierluigi Calanca; Andreas P. Weigel; Alexandra Weiss (Acta Geophysica, 2008)

The effect of mountainous topography on moisture exchange between the “surface” and the free atmosphere - Andreas P. Weigel; Fotini K. Chow; Mathias W. Rotach (Boundary-Layer Meteorology, 2007)

On the nature of turbulent kinetic energy in a steep and narrow Alpine valley - Andreas P. Weigel; Fotini K. Chow; Mathias W. Rotach (Boundary-Layer Meteorology, 2007)

Mean Flow and Turbulence Characteristics in an Urban Roughness Sublayer - Petra Kastner-Klein; Mathias W. Rotach (Boundary-Layer Meteorology, 2004)

An Urban Surface Exchange Parameterisation for Mesoscale Models - Alberto Martilli; Alain Clappier; Mathias W. Rotach (Boundary-Layer Meteorology, 2002)

Derivation Of Refractive Index And Temperature Gradients From Optical Scintillometry To Correct Atmospherically Induced Errors For Highly Precise Geodetic Measurements - Alexandra I. Weiss; Maria Hennes; Mathias W. Rotach (Surveys in Geophysics, 2001)

Simulation Of Urban-Scale Dispersion Using A Lagrangian Stochastic Dispersion Model - Mathias W. Rotach (Boundary-Layer Meteorology, 2001)